Modern individuality in Hegel's practical philosophy - Rózsa, Erzsébet (Critical studies in German idealism, 2012)
Modern individuality is the not-so-secret protagonist of Hegel's practical philosophy. In the framework of spirit, Hegel presents some basic features of the individual's way of life, lifeworld, self-interpreation, and self-determination, which can also be timely in shaping our own personal and social identities.